Identification of Thrombosis Risk in Patients with Suffering Cancer Conditions Undergoing Chemotherapy - Maylín Jiménez Abraham; Julio Dámaso Fernández Águila; Ana Lourdes Vasallo Díaz; Dayana Calzada Urquiola (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: there is an established relationship between cancer and the appearance and development of thromboembolic disease. It is necessary to identify patients with an increased risk of venous thromboembolism using predictive scales to individualize the risk. Objective: to identify the risk of thrombosis in patients with suffering cancer conditions undergoing chemotherapy. Method: a series of cases descriptive cross-sectional study, treated at the Clinical Oncology Service of the Dr. Gustavo Aldereguía Lima University General Hospital, Cienfuegos, from June the 1st, 2020 to April 30th, 2021. The information was obtained from the clinical record and a data collection model. The variables analyzed were: age, sex, site of the primary tumor, platelet count prior to chemotherapy, serum hemoglobin levels, erythropoietin use, leukocyte count prior to chemotherapy, and body mass index. The data obtained were processed using the SPSS version 21 statistical program and the results are presented in tables using absolute numbers and percentages. Results: the most frequent age group was 60 years old and over with 77 patients (51.3 %), 45 (30 %) male. The application of the Khorana score marked a relevant percentage (26 %) of patients with intermediate and high risk of thrombosis. Conclusions: the research shows a mostly aged adult population, with risk factors for thrombosis related to the patient, oncological disease and systemic treatments.